2000
DOI: 10.1007/s11745-000-538-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of n−3 polyunsaturated fatty acid supplementation on lipid peroxidation of rat organs

Abstract: The present study was undertaken in order to reexamine the effect of n-3 polyunsaturated fatty acid (PUFA)-rich diet supplementation on lipid peroxidation and vitamin E status of rat organs. Male Wistar rats were fed a diet containing safflower or fish oil at 50 g/kg diet and an equal amount of vitamin E at 59 mg/kg diet (1.18 g/kg oil; and 1.5 g/kg PUFA in safflower oil diet, and 4.3 g/kg PUFA in fish oil diet) for 6 wk. Fatty acid composition of total lipids of brain, liver, heart, and lung of rats fed fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
1
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 45 publications
4
25
1
7
Order By: Relevance
“…In the study of rats fed safflower and fish oil diets for 6 wk, there were no significant differences in the thiobarbituric acid-reactive substances (TBARS), PC-OOH, or PE-OOH in the erythrocyte membranes among the groups (13). Under conditions when the rats underwent ferric nitrilotriacetic acid (Fe-NTA) oxidative stress, the increased level of TBARS in the livers was significantly higher in the fish oil diet group than in the safflower oil diet group; however, the 8-hydroxydeoxyguanosine (8-OHdG) level in the livers of the rats fed the fish oil diet group was remarkably lower than that in the livers of the safflower diet group (14).…”
Section: Discussionmentioning
confidence: 98%
“…In the study of rats fed safflower and fish oil diets for 6 wk, there were no significant differences in the thiobarbituric acid-reactive substances (TBARS), PC-OOH, or PE-OOH in the erythrocyte membranes among the groups (13). Under conditions when the rats underwent ferric nitrilotriacetic acid (Fe-NTA) oxidative stress, the increased level of TBARS in the livers was significantly higher in the fish oil diet group than in the safflower oil diet group; however, the 8-hydroxydeoxyguanosine (8-OHdG) level in the livers of the rats fed the fish oil diet group was remarkably lower than that in the livers of the safflower diet group (14).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, polyphenols also could exert cardiovascular benefits by altering the lipid profiles of plasma and liver [28]. Many studies have proved that consuming high dose of n-3 PUFA could lead to the decreased antioxidant contents and increased possibility of lipid oxidation in tissues, blood, and urine due to the increase of PUFA in membrane lipids of human and animals [29]. Our studies indicated that rats fed CFO had higher plasma T-AOC, vitamin E content, GSH, SOD, and GPX activities than those fed HRFO.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid composition of total lipids in isolated liver of the fish oil diet group was n-3 PUFA rich and that in the safflower oil diet group was n-6 PUFA rich. 5) Hepatocytes were incubated with ADP/Fe(II) ion or hydrogen peroxide to induce oxidative stress in vitro. The degree of lipid peroxidation of oxidized hepatocytes was assessed based on the levels of the phospholipid hydroperoxides PCOOH and PEOOH and the levels of TBARS.…”
Section: Resultsmentioning
confidence: 99%